All Days 2014
DOI: 10.2118/172453-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Gas Production Design in Gas Condensate Reservoir

Abstract: Optimal production of gas from gas condensate reservoirs have been a major concern to the petroleum industry. Enormous liquid dropout lost to the reservoir during depletion process has been found to restrict the flow of gas near the wellbore, thereby reducing wellbore productivity. The search for the optimal production strategy to produce gas and even the condensed liquid has resulted to the use of enhanced production technique such as gas cycling, water flooding or wettability alteration. Gas cycling is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The development of condensate blockage nearby the production wells can be considered as an additional skin [9]. Pressure maintenance, vaporization of the condensate components and wettability alteration are the considered methods to control the condensation in the reservoir [9], [10]. In this regard, there are various suggested techniques such as drilling horizontal wells, hydraulic fracturing before and after the formation of condensate bank, acidizing after the formation of condensate bank and dry gas injection for reducing the condensate amount in the reservoir [11], [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The development of condensate blockage nearby the production wells can be considered as an additional skin [9]. Pressure maintenance, vaporization of the condensate components and wettability alteration are the considered methods to control the condensation in the reservoir [9], [10]. In this regard, there are various suggested techniques such as drilling horizontal wells, hydraulic fracturing before and after the formation of condensate bank, acidizing after the formation of condensate bank and dry gas injection for reducing the condensate amount in the reservoir [11], [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Well producing scheme may impose significant influence on the phase behaviour i.e. pressure depletion creates two phase flow which impacts reservoir performance [2,3]. In 2017, Ifeanyi and co-researcher [1] in their work showed that heavier hydrocarbon components in the gas, during the production of a gascondensate reservoir, drop out as liquid as reservoir pressure drops below the fluid dew point pressure.…”
Section: Introductionmentioning
confidence: 99%